Zakat Refund Program: a preliminary study of its implementation in PPZ MAIWP - Samad, Khairunnisa; Khalid, Haniza (2013)
In its efforts to improve zakat collection rates in Wilayah Persekutuan, Malaysia, Pusat Pungutan Zakat (PPZ MAIWP), has implemented an introduced a ‘Zakat Refund’ scheme in which a certain proportion of the zakat paid may be refunded to the payer for him to directly distribute to eligible asnafs. The purpose of this study is to explore the motivation and structure of the PPZ zakat refund program as well as the perception of zakat payers on its implementation. To this end, we employ qualitative approach framed within a case study methodology i.e. of the PPZ and its zakat refund participants. The data were collected through corporate documentation, brochures and semi-structured interviews either through face-to-face or email interviews. Our findings show that since the introduction of the zakat refund program, zakat collections have increased significantly, particularly from companies and high net worth individuals. Our interviews revealed that the companies are enthusiastic about carrying out zakat distribution themselves as an extension of their Corporate Social Responsibility activities. The outcome of the study inaugurates opportunities for future research in large-scale sampling and also the comparison of the zakat refund practices in other states as well as other regions if any.